Proinflammatory Stem Cell Signaling in Cardiac Ischemia - Herrmann, Jeremy L. (Mary Ann Liebert, Inc., 2009)
Cardiovascular disease remains a leading cause of mortality in developed nations, despite continued advancement in modern therapy. Progenitor and stem cell–based therapy is a novel treatment for cardiovascular disease, and modest benefits in cardiac recovery have been achieved in small clinical trials. This therapeutic modality remains challenged by limitations of low donor-cell survival rates, transient recovery of cardiac function, and the technical difficulty of applying directed cell therapy. Understanding the signaling mechanisms involved in the stem cell response to ischemia has revealed opportunities to modify directly aspects of these pathways to improve their cardioprotective abilities. This review highlights general considerations of stem cell therapy for cardiac disease, reviews the major proinflammatory signaling pathways of mesenchymal stem cells, and reviews ex vivo modifications of stem cells based on these pathways. Antioxid. Redox Signal. 11, 1883–1896.